Original article Association of interleukin 13 promoter gene polymorphism with atopic dermatitis - Gleń, Jolanta; Nedoszytko, Bogusław; Jasiel-Walikowska, Elżbieta; Wilkowska, Aleksandra; Zabłotna, Monika; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Interleukin 13 (IL-13) is a major cytokine involved in IgE synthesis, increased levels of which are observed in the majority of atopic dermatitis (AD) patients. The IL-13 gene has been mapped to the cytokine cluster on chromosome 5q31-33, which has been associated with atopic conditions. Numerous single-nucleotide polymorphisms (SNP) have been identified in the IL-13 gene and have been found to be associated with IgE levels and/or allergic diseases. Recently, polymorphism (C to T exchange) at position -1024 of the promoter region in the IL-13 gene has been described. Some reports indicate that these polymorphisms are associated with allergic asthma, altered regulation of IL-13 production and increased binding of nuclear proteins to this region. The aim of this study was to analyse the association of IL-13 gene polymorphism at position -1024 C/T in patients with atopic dermatitis. In our study we analysed 111 patients with AD and 65 healthy controls. The polymorphism -1024 C/T in the promoter region of the IL-13 gene was typed using ARMS-PCR method. We found that -1024T allele and CT genotypes frequency were significantly higher among patients with atopic dermatitis in comparison with control subjects (55% vs 31%; OR, 2, 1, p<0.028). In conclusion, our results indicate that presence of -1024 C/T polymorphism of IL-13 gene may predispose to the development of atopic dermatitis in the northern Polish population.